Implicações subjetivas da definição biológica e judicial da paternidade: efeitos do psicanalista no Tribunal de Família - Mônica Campos Silva (2011)
In this work we investigate the biological implications of subjective decision and legal paternity. From the notion of father in Freud and Lacan, we discuss the importance of fatherhood in the subjects constitution: its structural effects, as well as the use that can be made of this tool. In this same route, confronted to the contemporary and scientific advances, which may affirm the biological origin of each one, we seek to address the major aspects that involve the formation of a family to a subject and the nomination that the latter makes of the paternal and maternal functions. After delimitating the question what is to be a father? in Psychoanalysis, and from the analytical practice in family court, we question the treatment given to this issue by the fields of law and science. Our reflection sought to extract what kinds of effects, mainly subjective, a procedural action of paternity denial and, consequently, the judicialization of fatherhood, can cause for those involved. We consider that a breach of promise, without any treatment, even if it does not interfere with the subjective inscription, can bring a decline of belief in the paternal semblant, as well as deadly effects. In this sense, we aim to outline what the psychoanalyst can offer in his practice in the family court. We reach the end of our work proposing the hypothesis according to which, when we specify this practice transferring its status from necessary to contingent as one that responds with not knowing when convened to evaluate, we establish that only by supporting the real at stake , the unapproachable for the subject, a solution will be able to arise, an invention proper to each one.